Duffing oscillators for secure communication. (October 2018) - Zaher, Ashraf A.
Abstract: This paper introduces a new technique for using chaotic Duffing oscillators in secure communication. The secret message is encrypted using the parameters of the Duffing oscillator that indirectly affect the generated chaotic orbits. The mathematical model of the chaotic transmitter uses three parameters that can be altered between two levels, depending on the binary sequence of the digital secret message and the corresponding cipher. Consequently, a total of eight chaotic attractors are used to scramble the binary-based signal. Two different structures, for the synchronization and encryption mechanisms, between the transmitter and the receiver, are introduced. The first one uses the time series of the two chaotic signals generated by the Duffing transmitter, while implementing a cipher-less encryption mechanism. The second one uses a single time series of the Duffing transmitter, while allowing one of its parameters to act as a digital cipher. Better utilization of the communication channel is proved for the second method, while using a new adaptive Lyapunov-based technique to implement both the state synchronization and the parameters estimation at the receiver side. Both simulation and experimental case studies are presented to illustrate the proposed techniques and their applicability to securely transmit various multimedia digital signals.